The Early “Unnatural” History Following Surgical Repair of Ventricular Septal Defects - Chikkabyrappa, Sathish M.; Tretter, Justin T.; Doshi, Arpan R.; Buddhe, Sujatha; Bhatla, Puneet; Ludomirsky, Achi (Kansas Journal of Medicine, 2019)
Introduction Surgical outcomes for simple ventricular septal defects (VSD) have been excellent in the past three decades. For this project, the timing of resolution of left-sided dilation and mitral regurgitation (MR) following VSD repair was assessed. Methods Echocardiographic data surrounding surgery of 42 consecutive children who underwent surgical patch repair of a VSD were reviewed. The echocardiograms were reviewed up to a mean of 12 months post-operatively (range 9 - 14 months). Quantitative data indexed to body surface area including left atrial (LA) volume, mitral valve annulus diameter, and left ventricular end-diastolic dimension (LVEDD) was analyzed. Results The majority of our pre-surgical cohort had only trace (44%) or no MR (31%), with a small proportion having mild (16%) or moderate MR (9%). No patients had moderate or greater MR following repair at follow-up. The median mitral valve annular Z-score was 1.8 (SD 1.6; range: -1.2 to 4.1) pre-operatively, improving to a 0.6 (range: -1.7 to 2.4; p < 0.001) at follow-up. LA dilation was present in 70% of patients, with a median LA volume Z-score of 1.1 (range: -2.6 to 15.5), decreasing to 13% median Z-score -1.2 (range: -3.5 to 2.9; p < 0.001) at follow-up. LV dilation was present in 81% of pre-operative patients with a median LVEDD Z-score of 3.0 (range: -2.0 to 7.9). There was significant improvement in qualitative assessment of LV enlargement (25%) with a median LVEDD Z-score of 0.5 (range: -2.1 to 2.9; p < 0.001) at follow-up. Discharge echocardiogram was performed at a mean of 5.7 days (range: 3 - 12 days) following surgery. Conclusions Normalization of LA, mitral valve annulus, and LV size occurred within the first three months in the majority of patients, with significant changes occurring within the first post-operative week following surgical repair for VSD.